2019
DOI: 10.1002/smll.201902141
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir–Blodgett Nanowire Devices for In Situ Probing of Zinc‐Ion Batteries

Abstract: In situ monitoring the evolution of electrode materials in micro/nano scale is crucial to understand the intrinsic mechanism of rechargeable batteries. Here a novel on‐chip Langmuir–Blodgett nanowire (LBNW) microdevice is designed based on aligned and assembled MnO2 nanowire quasimonolayer films for directly probing Zn‐ion batteries (ZIBs) in real‐time. With an interdigital device configuration, a splendid Ohmic contact between MnO2 LBNWs and pyrolytic carbon current collector is demonstrated here, enabling a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Some studies have successfully proved that β-MnO 2 has excellent zinc storage performance. [86][87][88][89] A previous study by Kang et al 90 revealed that massive β-MnO 2 delivered low electrochemical activity in ZIBs. In a subsequent work, Kang et al 91 achieved reversible insertion/extraction of Zn 2+ ions into/from β-MnO 2 with a porous framework.…”
Section: Manganese Dioxidementioning
confidence: 97%
See 3 more Smart Citations
“…Some studies have successfully proved that β-MnO 2 has excellent zinc storage performance. [86][87][88][89] A previous study by Kang et al 90 revealed that massive β-MnO 2 delivered low electrochemical activity in ZIBs. In a subsequent work, Kang et al 91 achieved reversible insertion/extraction of Zn 2+ ions into/from β-MnO 2 with a porous framework.…”
Section: Manganese Dioxidementioning
confidence: 97%
“…In these structures, the basic structural unit MnO 6 octahedra is connected to each other by co‐angle/co‐edge, constructing chain, tunnel, layered structures with enough space accommodating foreign cations . Given this structural advantage, MnO 2 has been extensively investigated as favorable cathodes for batteries in the past several years, including Li‐ion batteries, Na‐ion batteries, K‐ion batteries, Mg‐ion batteries, and latest ZIB . Theoretically, MnO 2 can accommodate one Zn 2+ insertion per formula with a high theoretical capacity of approximately 616 mAh/g, in which the Mn 4+ is reduced to Mn 2+ .…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, another commonly used MnO 2 materials were also studied. For example, Liu et al [270] fabricated the MnO 2 nanowire (Figure 17b) to construct a novel on-chip Langmuir-Blodgett nanowire (LBNW) micro device for directly probing Zn-ion batteries in real-time. For the first time, they revealed the conductance of MnO 2 LBNW monotonically increase/decrease upon the charge/discharge process.…”
Section: Other Dimensional Materialsmentioning
confidence: 99%